RUANG TAFSIR ATAS JENIS/BENTUK SENGKETA PEMILIHAN KEPALA DAERAH YANG DAPAT DIAJUKAN KE PENGADILAN TINGGI TATA USAHA NEGARA - Kartabrata, Fajar Ramadhan; Tedjabuwana , Rosa (Jurnal Keadilan Pemilu, 2023)
Referring to Law No.10/2016 and its subsequent regulations, dispute settlement for Local Government Election is jurisdiction of BAWASLU, and its verdict is considered binding. However, at the same time the Hight Administrative Court (PTUN) is given jurisdiction for administrative dispute of Local Government Election. These two conflicting rules come to attention because the enactment of the verdict of Local/District General Election Commission (KPU Provinsi dan Kota/Kabupaten). This creates confusion in the application of these regulations because there are no clear parameters for disputes that can be qualified as Local Government Election Administrative Disputes. Thus, the formulation of norms regarding issues regarding the implementation of Local Government Elections, especially regarding Election Disputes and State Administration Election Disputes, needs to be adjusted to the system applied in resolving Process Disputes and State Administration Disputes in the Implementation of General Elections as stipulated in Law Number 7/2017 regarding General Elections.